CONTENT OF INDEPENDENT WORK IN THE FORMATION OF LEARNING AND COGNITIVE COMPETENCE OF FUTURE TEACHERS (Conference Zone, 2022)
This article gives you a brief overview on independent learning. The futureFeatures of independent work in the formation of teaching competencies of teachersis about.